The Stock Market and the Financing of Corporate Growth in Africa : The Case of Ghana - Yartey, Charles Amo (IMF Working Papers; Working Paper ;, 2006)
This paper examines the corporate financing pattern in Ghana. In particular, it investigates whether Singh's theoretically anomalous findings that developing country firms make considerably more use of external finance and new equity issues than developed country firms to finance asset growth hold in the case of Ghana. Replicating Singh's methodology, our results show that compared with corporations in advanced countries, the average listed Ghanaian firm finances its growth of total assets mainly from short-term debt. The stock market, however, is the most important source of long-term finance for listed Ghanaian firms. Overall, the evidence in this paper suggests that the stock market is a surprisingly important source of finance for funding corporate growth and that stock market development in Ghana has been important.